APAKAH KEBERADAAN BALITA MENENTUKAN PARTISIPASI KERJA PEREMPUAN KAWIN USIA SUBUR? ANALISIS SAKERNAS AGUSTUS 2019 - Rini Sulistyowati (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2021)
Women's labor participation has been stagnant for decades in Indonesia. Several research concluded that there was a large contribution from labor participation of married women and the presence of children in the household to the dynamics of women's labor participation. This study aims to see the relationship between the existence of children under five and the labor participation of married women aged 20-49 years. Using Sakernas August 2019, the results of descriptive statistics reveal that 40% of married women aged 20-49 years choose to not be in the laborforce. It’s mainly contributed by those who live with children under five. When entering the labor market, married women aged 20-49 years who live with toddlers are more likely to work part-time, both voluntarily and involuntarily (underemployment). Another interesting finding is that one of five married women aged 20-49 years who are not part of the labor force and who live with toddlers still have the desire to work.